ANALISIS SWOT STRATEGI PEMERINTAH DAERAH KABUPATEN BANDUNG DALAM PENANGANAN KONFLIK HORIZONTAL ORGANISASI MASYARAKAT DI KABUPATEN BANDUNG - Rendy Adiwilaga; mustofa, Mustabsyirotul Ummah Mustofa; Kansah Eka Permana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
Mass or Community Organizations (Ormas) in principle represent an established and healthy democratic life, because the existence of mass organizations is included in the category of freedom of association and assembly for the community. Unfortunately, many Civil Society Organizations (CSOs) are involved in conflicts of interest which lead to open violence, including the Bandung Regency which has a fairly high productivity of CSO establishments. This study uses a SWOT analysis which contains the variables of strengths, weaknesses, opportunities and threats, and a qualitative method with a case study approach. The results of the study show that from the aspect of strength, the local government is represented by Kesbangpol as a work unit that has direct contact with Ormas, the first of which is support from